Factors associated with COVID-19 vaccine confidence among primary care providers in Kazakhstan, March–April 2021 - Nabirova, Dilyara; Horth, Roberta; Kassabekova, Lena; Henderson, Alden; Yesmagambetova, Aizhan; Alaverdyan, Sevak; Nuorti, J. Pekka; Smagul, Manar (Frontiers in Public Health, 2023)
Introduction Vaccination is a critical public health intervention, and vaccine hesitancy is a major threat. Globally, confidence in COVID-19 vaccines has been low, and rates of routine immunizations decreased during the COVID-19 pandemic. Because healthcare providers are a trusted source of information on vaccination in Kazakhstan, it was vital to understand their knowledge, attitudes and practices (KAP) related to both routine and COVID-19 vaccines. Methods From March to April 2021, we conducted a cross-sectional study among the healthcare providers responsible for vaccination in 54 primary care facilities in three cities in Kazakhstan. All consenting providers anonymously completed structured online questionnaires at their place of work. A provider was classified as having COVID-19 vaccine confidence if they planned to get a COVID-19 vaccine, believed that COVID-19 vaccines are important to protect their community and either believed the vaccine was important to protect themselves or believed that getting a vaccine was safer than getting COVID-19. Statistical analysis included chi-square, Spearman’s rank correlation coefficient, and Poisson regression. Results Of 1,461 providers, 30% had COVID-19 vaccine confidence, 40% did not, and 30% would refuse vaccination. Participants were mostly female (92%) and ≤ 35 years old (57%). Additionally, 65% were nurses, 25% were family physicians, and 10% were pediatricians. Adequate KAP for routine vaccines was low (22, 17, and 32%, respectively). Adequate knowledge was highest among pediatricians (42%) and family physicians (28%) and lowest among nurses (17%). Misconceptions about vaccines were high; 54% believed that influenza vaccines cause flu, and 57% believed that there is a scientifically proven association between vaccination and autism and multiple sclerosis. About half (45%) of the practitioners felt confident answering patient vaccine-related concerns. In adjusted models, COVID-19 vaccine confidence was positively associated with adequate knowledge of vaccines (prevalence ratio: 1.2, 95% confidence interval: 1.0–1.4) and adequate attitudes related to routine vaccines (3.1, 2.7–3.6). Conclusion Our study uncovers critical areas for interventions to improve KAP related to routine immunizations and COVID-19 vaccine confidence among providers in Kazakhstan. The complex relationship between KAP of routine vaccines and COVID-19 vaccine confidence underscores the importance of addressing vaccine hesitancy more broadly and not focusing solely on COVID-19.